Detection of the Trp-2027-Cys Mutation in Fluazifop-P-butyl–resistant Itchgrass (Rottboellia cochinchinensis) using High-Resolution Melting Analysis (HRMA). Issue 3 (2nd April 2018) - Barrantes-Santamaría, Walter; Castillo-Matamoros, Rolbin; Herrera-Murillo, Franklin; Brenes-Angulo, Arturo; Gómez-Alpízar, Luis
Abstract: Itchgrass [ Rottboellia cochinchinensis (Lour.) Clayton] is recognized as one of the most noxious and troublesome annual weeds in tropical and subtropical regions. Acetyl-coenzyme A carboxylase (ACCase)-inhibiting herbicides have been frequently used for managing R. cochinchinensis POST in a variety of crops, resulting in evolved resistance to these herbicides. Recently, resistance to fluazifop-P-butyl has been demonstrated for this weed, as the result of a G-to-C single-nucleotide polymorphism (SNP) that leads to the Trp-2027-Cys substitution in the ACCase enzyme. This study was conducted to develop a high-resolution melting analysis (HRMA) for the detection of the mutation underlying the Trp-2027-Cys substitution. The HRMA assay allowed differentiating between fluazifop-P-butyl–resistant (C mutant) and susceptible (G wild type) R. cochinchinensis plants. HRMA accuracy was confirmed with DNA sequencing of the target-site mutation, and no false positives or negatives were observed. Our results illustrated how HRMA is effective detecting the Trp-2027-Cys substitution in an R. cochinchinensis resistance, and how this technique can be of great value for developing high-throughput programs for monitoring evolution and dispersion of target site–based herbicide resistance at large scales.